The Effect of Rice Productivity on Farmers' Welfare and Food Crop Investment in Indonesia - Nurina Endra Purnama; Darwati Susilastuti; Pudji Astuty (Jurnal Multidisiplin Indonesia, 2025)
Rice is a fundamental staple in Indonesia, playing a vital role in both the diet of the population and the agricultural economy. As rice productivity influences not only food security but also the economic well-being of farmers, understanding this relationship is crucial for developing effective agricultural policies. Enhanced productivity can lead to increased income for farmers, which in turn can foster greater investment in food crop production and improve overall agricultural sustainability. The study aims to determine how improvements in rice productivity influence the economic well-being of farmers and their investment decisions in food crops. Utilizing the Error Correction Model (ECM) for data analysis, the research examines both short-term and long-term relationships between rice productivity, farmers' welfare, and food crop investment. The findings reveal that increased rice productivity significantly enhances farmers' welfare, leading to higher levels of investment in food crops. These results highlight the importance of improving rice productivity as a strategy to promote agricultural development and improve the livelihoods of farmers in Indonesia.